2023
DOI: 10.1099/mgen.0.001063
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic comparisons reveal a highly diverse and unique viral community in a seasonally fluctuating hypersaline microbial mat

Abstract: In spring 2016, a shallow hypersaline pond (50×25 m) was found in the Cuatro Cienegas Basin (CCB). This pond, known as Archaean Domes (AD) because of its elastic microbial mats that form dome-shaped structures due to the production of reducing gases reminiscent of the Archaean eon, such as methane and hydrogen sulfide, harbour a highly diverse microbial community, rich in halophilic and methanogenic archaea. AD is a seasonally fluctuating hypersaline site, with salinity ranging from low hypersaline (5.3%) duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Such diversity is believed to have evolved as a result of the long-standing environmental stability of a deep aquifer that recreates an ancient ocean conditions, and which nourishes the aquatic systems of Cuatro Ciénegas Basin through the movement of groundwater produced by the magmatic pouch deep in the Sierra San Marcos y Pinos [59]. Specifically, the environment from which samples were extracted is a shallow pond characterized by high pH and salinity known as Archaen Domes [16, 17, 18]. It has been shown that Archaean Domes harbors a great diversity of bacteria on a short spatial scale [17] and is one of the most diverse archaeal communities in the world [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such diversity is believed to have evolved as a result of the long-standing environmental stability of a deep aquifer that recreates an ancient ocean conditions, and which nourishes the aquatic systems of Cuatro Ciénegas Basin through the movement of groundwater produced by the magmatic pouch deep in the Sierra San Marcos y Pinos [59]. Specifically, the environment from which samples were extracted is a shallow pond characterized by high pH and salinity known as Archaen Domes [16, 17, 18]. It has been shown that Archaean Domes harbors a great diversity of bacteria on a short spatial scale [17] and is one of the most diverse archaeal communities in the world [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of consistency of CrisprOpenDB and RaFAH with the other methods suggests that relying on a >11 million spacers database [5] or on a Random Forest classifier based on the protein content of viruses with known host [11], respectively, may be beneficial only when the hosts or the assembled viruses are already known, or are closely related to hosts or viruses represented in the corresponding databases. Therefore, for highly diverse datasets likely to have a high proportion of novel viruses as the one tested here [18], it may be more appropriate to use host-based tools, either alignment-based or alignment-free, such as CrisprCustomDB or PHP, with ad hoc databases built with archaea and bacteria MAGs from the same dataset whenever possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This diversity includes a high abundance of halotolerant bacteria, as well as halophilic and methanogenic archaea, which are rare in the rest of the CCB [ 8 , 9 ]. Finally, a highly diverse viral community has recently been described, in which haloarchaeaviruses appear to be an essential component, and which does not behave like those from other hypersaline or high pH sites in the face of environmental fluctuations [ 10 ]. However, viruses in AD have yet to be fully characterised, which is essential to dissect the virus-host relationships and interactions that may drive microbial and viral diversity in such a unique site.…”
Section: Introductionmentioning
confidence: 99%